Understory plants in Mount Singai, Sarawak, Malaysia - Alexander Kiew, Sayok; McLellan, Joanna; Noweg, Gabriel Tonga; McLellan, Louisa; Khong, H.Y. (2011)
Mount Singai in Bau District was settled by BiSingai tribe for almost 300 years before they moved downhill to 14 villages some 40 years ago. They extracted forest products and planted crops in their clearings at the mountain. The documentation of these plants and impacts of these activities on their composition in the area would be an interesting discovery. A survey on understory plants at undertaken to determine these information. Two subplots of 2 m x 2 m were made in each of the 16 plots (50 m by 10m) established along the main trail to the mountain top. All understory plants including epiphytes were recorded in these subplots. Preliminary results show that a total of 1,148 understory plants comprising of 142 species from 66 families were recorded. Family Selaginellaceae with 174 individuals (15.16% of total) dominates while Apocynaceae with 75 and Euphorbiaceae with 70 individuals are a distant second and third respectively. Families Verbenaceae, Theaceae, Rhamnaceae and Icacinaceae were among the 11 families with one individual each and were considered the least. Seedlings of middle to upper canopy trees with 396 individuals (34.5%) dominate the type of plants recorded. Mosses (Selaginella canaliculata) with 170 individuals (14.8%) form a distant second. Most of the mosses are found at the foothills (62.4%) where the forest floor is moister. Almost all plants have uses for man apart from their ecological role. About 16% (182 plants) can be used for landscaping or has ornamental value while 10% (112 plants) for other uses (timber, cultural, and handicrafts) followed by 7% (83 plants) have medicinal values. The remainder 771 plants (67.1%) have overlapping or combining uses for food, medicinal, landscaping and others. Although the study was only undertaken along a single trail which traverses through an abandoned settled area and farms, plants at Mount Singai are considered abundant and that the locals activities and presence have little impact on the plants there. Because it was discovered that the plots set-up missed more than 15% of the species and 21% of the family, it was suggested that more or bigger subplots be established to capture most plants. Studies on different trails in Mount Singai are being planned to understand more on the understory plants there. Further analysis and characterisation on the data collected as well as information on their distribution and their relationships with some environmental variations in the area such as soils and microhabitats will also be undertaken.